A Messiah for the Third Millennium - Ford, David (Modern theology, 2000)
The first part explores briefly the significance of Jesus over two millennia. It then examines the relations of Christians and Jews, with special concentration on a theological alternative to the Christian supersessionism, which sees the church as superseding the Jews as the people of God. This is done through a plain sense of pragmatic reading of the Letter to the Ephesians in dialogue with the approach to scripture advocated by Peter Ochs. Finally, Nicholas de Lange's question, "Where was Jesus at Auschwitz?" is responded to through a theology of Jesus Christ facing Auschwitz, with implications for Christians and Jewish-Christian relations at the turn of the millennium.